2018
DOI: 10.1101/344127
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

G-quadruplex forming sequences in the genome of all known human viruses: a comprehensive guide

Abstract: G-quadruplexes are non-canonical nucleic acid structures that control transcription, replication, and recombination in organisms. G-quadruplexes are present in eukaryotes, prokaryotes, and viruses. In the latter, mounting evidence indicates their key biological activity. Since data on viruses are scattered, we here present a comprehensive analysis of putative G-quadruplexes in the genome of all known viruses that can infect humans. We show that the presence, distribution, and location of G-quadruplexes are fea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 65 publications
(80 reference statements)
0
35
0
Order By: Relevance
“…In both K562 and HepG2 cells, we observe similar enrichment for GRSF1 binding over 5' and 3' UTR pG4 sequences, leading us to speculate that a similar mechanism may exist to melt pG4 sequences, and promote degradation of their parent RNA transcripts in human cells. reported in the literature 36 , and G4-forming sequences have been found to occur commonly in multiple viral genomes 37 . This, coupled with the observation that RNA G4s appear to be universally depleted within prokaryotic transcriptomes 12 , makes it tempting to speculate that viruses may have evolved G4 sequences specifically as a mechanism for co-opting host cell machinery involved in gene expression and RNA regulation.…”
Section: Discussionmentioning
confidence: 98%
“…In both K562 and HepG2 cells, we observe similar enrichment for GRSF1 binding over 5' and 3' UTR pG4 sequences, leading us to speculate that a similar mechanism may exist to melt pG4 sequences, and promote degradation of their parent RNA transcripts in human cells. reported in the literature 36 , and G4-forming sequences have been found to occur commonly in multiple viral genomes 37 . This, coupled with the observation that RNA G4s appear to be universally depleted within prokaryotic transcriptomes 12 , makes it tempting to speculate that viruses may have evolved G4 sequences specifically as a mechanism for co-opting host cell machinery involved in gene expression and RNA regulation.…”
Section: Discussionmentioning
confidence: 98%
“…Local DNA structures have been shown to play important roles in basic biological processes, including replication and transcription Travers and Muskhelishvili, 2015;Surovtsev and Jacobs-Wagner, 2018). PQS analyses of human viruses have clearly demonstrated that these sequences are conserved also in the viral genomes (Lavezzo et al, 2018) and could be targets for antiviral therapies (Wang et al, 2015;Krafčíková et al, 2017;Ruggiero and Richter, 2018). For example, the conserved PQS sequence present in the L gene of Zaire ebolavirus and related to its replication is inhibited by interaction with G-quadruplex ligand TMPyP4, and this finding has led to suggestions that G-quadruplex RNA stabilization could constitute a new strategy against Ebola virus disease (Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…These have been detected in various This is a provisional file, not the final typeset article genomes, but most extensively they have been described in human genomes (Chambers et al, 2015;Bedrat et al, 2016;Hänsel-Hertsch et al, 2016). They are present also in viruses (Lavezzo et al, 2018;Frasson et al, 2019). G-quadruplexes probably play an important role in regulating replication in most viral nucleic acids (Lavezzo et al, 2018), and these structures have been suggested as targets for antiviral therapy (Métifiot et al, 2014;Ruggiero and Richter, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations